THE EFFECTIVENESS OF LEGAL PROTECTION FOR CHILDREN AS VICTIMS OF CYBERBULLYING WITHIN THE INDONESIAN LEGAL SYSTEM - Rini Setiawati; Benny Karya Limantara (RADJA PUBLIKA, 2026)
Advances in information and communication technology have brought various conveniences to individual life; however, they have also given rise to new forms of criminal activity, including cyberbullying. Such acts can carry psychological, social, and educational consequences, with children and adolescents being particularly vulnerable to becoming victims. This study aims to evaluate the effectiveness of legal protection measures for children who are victims of cyberbullying at SMA Negeri 9 Bandar Lampung, and to identify the factors that contribute to the effectiveness of those measures. The research employs a normative and empirical juridical approach, drawing on primary data obtained through interviews with the Deputy Head of Student Affairs of SMA Negeri 9 Bandar Lampung and the Women's and Children's Service Unit (PPA) of the Bandar Lampung Police, as well as secondary data obtained through literature review. The findings show that legal protection for minors who become victims of cyberbullying has been implemented through preventive and repressive measures. Prevention efforts include awareness campaigns, education on social media use, guidance, supervision, and the cultivation of moral values and legal awareness. Repressive measures, meanwhile, are implemented by handling both victims and perpetrators, providing assistance, mediation, and coaching, as well as facilitating the victim's recovery. Legal, law-enforcement, facility-related, societal, and cultural factors all contribute to the effectiveness of this legal protection.